Nurses' perception of the quality of the Rapid Response Team - Queiroz,Ágatha Stahl de (2019)
ABSTRACT Objective: verify the perception nurses have of the quality of the Rapid Response Team in the structure, process and outcome dimensions, as well as the influence of time of practice in the institution and the work shift of the professionals on this perception. Method: cross-sectional study, conducted between September and October 2016, with questionnaires to 55 nurses working in inpatient care units or members of the Rapid Response Team. The positive index and inferential tests were used in the data analysis. Results: a satisfactory positive index was identified in 25 of the 37 items analyzed, and the main frailties occurred in the process dimension. There was discrepancy in the perception of professionals with different length of time in the institution about medical consumables (p=0.05) and request for the Rapid Response Team (p=0.03), besides the work shift and communication among the members involved (p=0.02). Conclusion: the nurses' perception of the quality of the Rapid Response Team is satisfactory, especially in the areas of structure and outcome.